1995
DOI: 10.1139/v95-009
|View full text |Cite
|
Sign up to set email alerts
|

Electron exchange kinetics in a tetrahedrally coordinated copper(II)/(I) couple

Abstract: The four-coordinate anion Cul(dpym), (Hdpym = 3,3',5,5'-tetramethyl-4.4'-dicarboethoxydipyrromethene) can be prepared in solution in acetone either by electrochemical reduction of the known tetrahedral complex CuH(dpym)? (E' = -290 mV vs. SCE) or by the quantitative reaction of 2Hdpym with Cu(CH,CN),+ in the absence of 0,. The latter reaction does not go to completion in solvents that bind relatively strongly to CU' or that are poor proton acceptors. Ligand exchange between cu'(dpym),-and excess Hdpym in aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Takagi and Swaddle have been studying Cu(II/I) electron-exchange couples by NMR where the coordination geometries of Cu(I) and Cu(II) are constrained to be similar, the kinetic behavior is expected to follow the context of the moderately fast electron-transfer case, and no significant change in coordination number or coordination geometry was expected prior to the electron-transfer processes. 27,28 The gated electron-transfer process has been successfully interpreted by the square scheme, postulated by Rorabacher et al, as shown in Scheme 1. The theoretical studies of the gated electron transfer have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takagi and Swaddle have been studying Cu(II/I) electron-exchange couples by NMR where the coordination geometries of Cu(I) and Cu(II) are constrained to be similar, the kinetic behavior is expected to follow the context of the moderately fast electron-transfer case, and no significant change in coordination number or coordination geometry was expected prior to the electron-transfer processes. 27,28 The gated electron-transfer process has been successfully interpreted by the square scheme, postulated by Rorabacher et al, as shown in Scheme 1. The theoretical studies of the gated electron transfer have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated electron self-exchange rate constant of Cu(bid) 2 2+/+ is 0.16 kg mol -1 s -1 . Takagi and Swaddle have been studying Cu(II/I) electron-exchange couples by NMR where the coordination geometries of Cu(I) and Cu(II) are constrained to be similar, the kinetic behavior is expected to follow the context of the moderately fast electron-transfer case, and no significant change in coordination number or coordination geometry was expected prior to the electron-transfer processes. , …”
Section: Introductionmentioning
confidence: 99%
“…The complex dipyrromethene-Cu(II)-His 6 was described as distorted square-planar type [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…These geometries have smaller ligand-field stabilization energies than the commonly observed tetragonal or square-planar coordination geometries. Pseudotetrahedral Cu(II)N 4 complexes have been prepared using geometrically constraining ligands such as 4 , 5 , and 6 . The tridentate ligand tris(3,5-diisopropylpyrazolyl)borate, 7 , has recently been used to construct pseudo-C 3 v CuN 3 S analogues of the type I copper metalloenzymes .…”
Section: Introductionmentioning
confidence: 99%